1956
DOI: 10.1172/jci103311
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of Hydroxyproline in Patients With Rheumatic and Non-Rheumatic Diseases 1

Abstract: The amino acid hydroxyproline constitutes approximately 13 per cent of collagen (1, 2), and 1 to 2 per cent of elastin (2). It is present in no other protein of the body. For this reason, the determination of hydroxyproline has been utilized for the estimation of collagen in various animal tissues (3), and in the fibrinoid material of the subcutaneous nodule of rheumatoid arthritis (4).It is, at the present time, not clear whether in the diseases of the connective tissue, or "collagen diseases," significant al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

1964
1964
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(58 citation statements)
references
References 15 publications
4
52
0
2
Order By: Relevance
“…Studies of its metabolism have shown that the urinary excretion of OHP is related to bone matrix turnover (Prockop and Kivirikko, 1967). It is, thus, not surprising to find that OHP excretion is elevated in bone diseases where there is increased turnover such as some endocrine diseases and rheumatoid disease and in osseous metastatic cancer (Ziff et al, 1956;Benoit et al, 1963;Kivirrikko et al, 1964;Guzzo et a/., 1969). Guzzo et al, (1969) observed that the output of urinary hydroxyproline was increased not only with osseous but also with soft tissue metastases.…”
Section: Urinary Hydroxyprolinementioning
confidence: 99%
“…Studies of its metabolism have shown that the urinary excretion of OHP is related to bone matrix turnover (Prockop and Kivirikko, 1967). It is, thus, not surprising to find that OHP excretion is elevated in bone diseases where there is increased turnover such as some endocrine diseases and rheumatoid disease and in osseous metastatic cancer (Ziff et al, 1956;Benoit et al, 1963;Kivirrikko et al, 1964;Guzzo et a/., 1969). Guzzo et al, (1969) observed that the output of urinary hydroxyproline was increased not only with osseous but also with soft tissue metastases.…”
Section: Urinary Hydroxyprolinementioning
confidence: 99%
“…The other 30% is excreted via the urine. It has been suggested that the ratio of hydroxyproline excreted from the lung to that excreted from the urine is fairly constant; therefore, changes in collagen breakdown can be quantified by measuring the changes in the urine concentration of the prolyl-hydroxyproline peptide, which may reflect ineffective peptidase activity (10,11,12). However, no studies have investigated the correlations between the severity of clinical spasticity, Muscle Hydroxyproline (MH), and Urine Hydroxyproline (UH).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of collagen results in excretion of hydroxyproline in the urine (Ziff et al 1956). From injection of ^^C-proline into young rats, at least three distinct hydroxyproline pools were found, with half-lives of 1, 5, and 50 to 200 days respectively (Lindstedt and Prockop 1961).…”
Section: Hormonesmentioning
confidence: 99%
“…In urine 97% of the hydroxyproline exists as peptides (pro-OHpro and gly-pro-OHpro) (Schrohenloher et al 1958), and only 3% as the free imino acid (Ziff et al 1956). Actually only around 25% of the peptides derived from collagen degradation end up in the urine.…”
Section: Hormonesmentioning
confidence: 99%
See 1 more Smart Citation